Mānaba jātikē bām̐cātē habē paramāṇu yud'dha rukhatē habē - Chovanek (Bangladesh Peace Council, 1982)
High contrast, black and white image of hands blocking falling bomb Original title : মানব জাতিকে বাঁচাতে হবে ,পরমাণু যুদ্ধ রুখতে হবে Suggested translation: Human kind must be saved, nuclear war must be stopped PO-1393